Skulduggery Pleasant : THE FACELESS ONES - Landy, Derek (London, United Kingdom : HarperCollins Children's, 2007)
If you've read the previous Skulduggery books then you know what the Faceless Ones are - and if you know what the Faceless Ones are, then you can probably take a wild guess that things in this book are going to get awfully sticky for our skeletal hero and his young sidekick.
9-13 years.
Keywords: Wizards -- Juvenile fiction; Pleasant, Skulduggery (Fictitious character) -- Juvenile fiction